Additivity of Jordan elementary maps on standard rings - Ferreira, B.L.M.; Guzzo Jr., H.; Ferreira, J.C.M. (Algebra and Discrete Mathematics, 2014)
We prove that Jordan elementary surjective maps on standard rings are additive.